PROJECT MANAGEMENT ISSUES IN THE FIELD OF ECOLOGY: RATIONAL NATURE USE AND RESOURCE SAVING - Yu. G. Evdokimova (Publishing House of the State University of Management, 2020)
The largest environmental issues in Russia have been considered in the article, their relationship with the development trends of the country’s economy and the legacy of the Soviet period has been traced, the directions of projects in the field of ecology, as well as the problems of their implementation have been reviewed, these issues have been compared with the practice of environmental projects in developed countries. Today, as we see, the issue of ecology is not in last place. The negative impact of humanity on the environment has reached an alarming level. There is a constant update, as well as the development of new technologies and techniques to prevent environmental problems in the country. Successful implementation of environmental projects directly depends on the level of education and the involvement of the population in solving environmental issues.